Novel Features of Considerable Biologic Interest: the Fourth Amendment and the Admissibility of Abandoned DNA Evidence - Holland, Thomas D. (Science and Technology Law Review, 2019)
DNA has become a fixture of modern society, so much so that much of the recent debate on the so-called “CSI effect” was actually a debate on the extent to which the general public has come to expect that DNA will play a role in even the most routine criminal cases. Expectations notwithstanding, DNA is unarguably a powerful forensic tool, one that almost seems to beg for its own set of rules—a “genetic exceptionalism” perhaps. In no area is this more debated than in the realm of “abandoned DNA,” i.e., DNA that is abandoned in the course of everyday activities, often unconsciously and unwittingly. Abandoned DNA, like abandoned property generally, falls outside of the protection of the Fourth Amendment by virtue of having been abandoned, and it may be collected by law enforcement without the benefit of a warrant. Many scholars argue that abandoned DNA is particularly in need of an exception that would bring it within the Fourth Amendment’s protection rather than to exclude it like other abandoned property, but there is no ready legal analogue for such action, and we should be wary of crafting one. Abandoned DNA, as its name implies, has its legal roots deep in the soil of abandoned property, and the existing body of abandonedproperty law provides a workable framework with which to analyze DNA issues. In this regard, abandoned DNA differs very little from other unconsciously and unwittingly abandoned human markers, such as fingerprints. To adopt an exception whereby abandoned DNA is given Fourth Amendment protection leads logically to an unworkable end state. If protection is sought for DNA privacy, it needs to come through statute rather than shoehorning it in under the Fourth Amendment.